(untitled) (UNED Research Journal, 2018)
Costa Rica is the world’s leading exporter of fresh pineapple (Ananas comosus); associated with the pineapple’s agricultural production, comes the issue of agricultural waste and the interest in pineapple stubble as the main discarding material. We estimated the biomass that is generated from pineapple stubble, the costs associated with field management and identified the current treatment that this waste is given; as well as an initial analysis of strengths, weaknesses, opportunities and threats. It is estimated that the biomass of pineapple stubble for 43 000Ha of current crop is 4,282 x 106 tons/year on a wet basis (640 thousand ton/year dry base). The associated costs for management in the pineapple stubble field range between US 1 000 and US 2 500 by hectare, depending on the type of management; dry (chemical drying with Paraquat) or green handling (crushing of the green plant) and its incorporation into the ground. Within the economy of export of agricultural products is the second largest, behind the banana, since more than US 900 million are exposed annually (2017), which makes it possible to add another biomass, such as banana, coffee, oil palm and forest products, to the development of a bioenergy and bio manufacturing industry. It is important that the biorefinery processes are integrated into industrial ecology models or circular economy, to minimize the production of greenhouse gases and allow food security in the regions, with the aim of achieving the objectives of sustainable development.